The Architectonicidae and Mathildidae (Gastropoda, Heterobranchia) of the Miocene Paratethys Sea—victims of the Miocene Climatic Transition - Harzhauser, Mathias; Landau, Bernard (Zootaxa, 2023)
The Architectonicidae of the Miocene of the Central Paratethys Sea comprise 18 species placed in eight genera. The coeval Mathildidae are documented by nine species, placed into three genera. We present descriptions of these species and illustrate type material wherever possible. Several species suggest relationships with Late Miocene to Holocene species of the Mediterranean Sea, although none of the species is known from modern faunas. Both families attained their maximum diversity during the early Middle Miocene (Langhian), and both families experienced a dramatic loss in species richness at the Langhian/Serravallian boundary. This Architectonicidae/Mathildidae turnover evidently coincided with the Miocene Climatic Transition, suggesting climate as the driving force. As members of both families feed on coelenterates, we assume that the climatic cooling of that phase caused a retreat of cnidarians, which is reflected in a decline in their predators. Ammotectonica nov. gen., Simplexollata nov. gen. and Pseudotuba nov. gen. are introduced as new genera. Ammotectonica gregorovae nov. sp., Simplexollata anticollata nov. sp., Nipteraxis deformatus nov. sp., Solatisonax? transversa nov. sp., Heliacus globosus nov. sp., Solatisonax tavianii nov. sp., and Pseudotorinia grasemanni nov. sp. are described as new species. Solarium (Torinia) criticum Boettger, 1907 and Discohelix quinquangularis Boettger, 1902 are treated as subjective junior synonyms of Heliacus berthae (Boettger, 1902) and Spirolaxis cornicula (Boettger, 1902).